Characterization of an Acidic Chitinase from Seeds of Black Soybean (Glycine max (L) Merr Tainan No. 3) - Chang, Ya-Min (PLoS One, 2014)
Using 4-methylumbelliferyl-β-D-N,N′,N″-triacetylchitotrioside (4-MU-GlcNAc(3)) as a substrate, an acidic chitinase was purified from seeds of black soybean (Glycine max Tainan no. 3) by ammonium sulfate fractionation and three successive steps of column chromatography. The purified chitinase was a monomeric enzyme with molecular mass of 20.1 kDa and isoelectric point of 4.34. The enzyme catalyzed the hydrolysis of synthetic substrates p-nitrophenyl N-acetyl chitooligosaccharides with chain length from 3 to 5 (GlcNAc(n), n = 3-5), and pNp-GlcNAc(4) was the most degradable substrate. Using pNp-GlcNAc(4) as a substrate, the optimal pH for the enzyme reaction was 4.0; kinetic parameters K (m) and k(cat) were 245 µM and 10.31 min(−1), respectively. This enzyme also showed activity toward CM-chitin-RBV, a polymer form of chitin, and N-acetyl chitooligosaccharides, an oligomer form of chitin. The smallest oligomer substrate was an N-acetylglucosamine tetramer. These results suggested that this enzyme was an endo-splitting chitinase with short substrate cleavage activity and useful for biotechnological applications, in particular for the production of N-acetyl chitooligosaccharides.